2022
DOI: 10.3390/metabo12111123
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ceramide Concentrations in Full-Term Pregnancies Complicated with Gestational Diabetes Mellitus: A Case-Control Study

Abstract: Ceramides, a sphingolipid group that acts as a messenger in cellular differentiation, proliferation, apoptosis and senescence, have been associated with cardiovascular disease and type 2 diabetes. The evidence for an association between ceramides and gestational diabetes mellitus (GDM) is scarce. This case-control study aimed to compare women with GDM with healthy, pregnant women in terms of plasma ceramide concentrations at the time of delivery. Ninety-two pregnant women were included in this case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…Changes in specific ceramide concentrations (increased 18:0, 18:1 and decreased ceramide 24:0) in early pregnancy increase the risk of GDM [77]. Decreased ceramide 24:0 concentrations were reported in the only study in full-term pregnancies complicated by GDM [26]. Although epidemiological studies have suggested that lipid metabolic profiles differ between women with and without GDM [78], most suffer from reverse causation bias and rarely study the first trimester of pregnancy, which is crucial for the development of GDM.…”
Section: Ceramides In Gestational Diabetes Mellitusmentioning
confidence: 89%
See 1 more Smart Citation
“…Changes in specific ceramide concentrations (increased 18:0, 18:1 and decreased ceramide 24:0) in early pregnancy increase the risk of GDM [77]. Decreased ceramide 24:0 concentrations were reported in the only study in full-term pregnancies complicated by GDM [26]. Although epidemiological studies have suggested that lipid metabolic profiles differ between women with and without GDM [78], most suffer from reverse causation bias and rarely study the first trimester of pregnancy, which is crucial for the development of GDM.…”
Section: Ceramides In Gestational Diabetes Mellitusmentioning
confidence: 89%
“…These responses render them relevant to many diseases. Ceramides potentially contribute to the pathogenesis of various autoimmune conditions, including rheumatic diseases and psoriasis, and cardiovascular and metabolic disorders, such as insulin resistance, diabetes, and gestational diabetes [2,6,[19][20][21][22][23][24][25][26]. Emerging evidence suggests an association with cancer through epigenetic mechanisms and psychiatric disorders [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we observed a positive association between maternal BMI and a lipid biomarker, Cer(D18:1/16:0), which is one of the most well-studied and validated lipid biomarkers predictive of morbidity and mortality, including GDM [ 59 ]. A nested case-control study from a prospective cohort of pregnant females identified that high Cer18:1 was associated with higher GDM risk [ 60 ]. Another study demonstrated that Cer18:1 concentration was higher among females who eventually developed GDM, compared with females with normal glucose tolerance [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of sphingosine 1-phosphate and ceramides on endothelial function and vasodilation have been evaluated and found to be critical for a healthy pregnancy [ 20 , 21 ]. Lipids, such as S1P mediate the endothelial effects of high-density lipoprotein (HDL).…”
Section: Discussionmentioning
confidence: 99%